2021
DOI: 10.9734/jpri/2021/v33i43a32499
|View full text |Cite
|
Sign up to set email alerts
|

In-silico Inhibitory Potential of Triphala Constituents Against Cytochrome P450 2E1 for the Prevention of Thioacetamide-induced Hepatotoxicity

Abstract: Background: Triphala, which is a combination of fruits of Terminalia chebula, Terminalia bellerica and Embilica officinalis generally recommended as herbal drug formulation in the Indian traditional medicine system. Study Design: To study the in-silico inhibitory potential of Triphala constituents against cytochrome P450 2E1 (CYP2E1) for the prevention of Thioacetamide-induced Hepatotoxicity Place and Duration of Study: The work has been performed at MUP's College of Pharmacy (B Pharm), Degaon, Ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In order to aid molecular docking, a three-dimensional grid box (size_x = 41.7862652138Å; size_y = 39.1754565902Å; size_z = 37.1398050256Å) with an exhaustiveness value of eight was developed [ 34 ]. The strategy reported in previous papers was used in order to carry out the complete molecular docking method as well as to locate cavities and active amino acid residues [ 18 , 28 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. The exposed cavity of the DHFR is shown with the co-crystallized ligand molecule in Figure 4 .…”
Section: Methodsmentioning
confidence: 99%
“…In order to aid molecular docking, a three-dimensional grid box (size_x = 41.7862652138Å; size_y = 39.1754565902Å; size_z = 37.1398050256Å) with an exhaustiveness value of eight was developed [ 34 ]. The strategy reported in previous papers was used in order to carry out the complete molecular docking method as well as to locate cavities and active amino acid residues [ 18 , 28 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. The exposed cavity of the DHFR is shown with the co-crystallized ligand molecule in Figure 4 .…”
Section: Methodsmentioning
confidence: 99%
“…There were active amino acid residues found by using the BIOVIA Discovery Studio Visualizer. The complete molecular docking technique, including identifying cavity and active amino acid residues, was carried out using the strategy described by Khan et al [26][27][28][29][30][31][32][33][34]…”
Section: Molecular Dockingmentioning
confidence: 99%
“…The research gave very promising inhibiting efficacy of Triphala in terms of binding affinity towards the chosen target. The study suggested that in future, these molecules can be used to overcome cancer in association with oxidative stress emerging from the abnormally increased activity of CYP2E1 [51].…”
Section: Studies On Triphalamentioning
confidence: 99%